8 Math Algebraic Expressions
8 Math Algebraic Expressions
8 Math Algebraic Expressions
Algebraic Expressions
1. Expressions are formed from variables and constants.
2. Terms are added to form expressions. Terms themselves are formed as product
of factors.
3. Expressions that contain exactly one, two and three terms are called monomials,
binomials and trinomials respectively. In general, any expression containing one or
more terms with non-zero coefficients (and with variables having non- negative ex-
ponents) is called a polynomial.
4. Like terms are formed from the same variables and the powers of these variables
are the same, too. Coefficients of like terms need not be the same.
5. While adding (or subtracting) polynomials, first look for like terms and add (or
subtract) them; then handle the unlike terms.
6. There are number of situations in which we need to multiply algebraic expres-
sions: for example, in finding area of a rectangle, the sides of which are given as ex-
pressions.
7. A monomial multiplied by a monomial always gives a monomial.
8. While multiplying a polynomial by a monomial, we multiply every term in the
polynomial by the monomial.
9. In carrying out the multiplication of a polynomial by a binomial (or trinomial), we
multiply term by term, i.e., every term of the polynomial is multiplied by every term
in the binomial (or trinomial). Note that in such multiplication, we may get terms in
the product which are like and have to be combined.
10. An identity is an equality, which is true for all values of the variables in the
equality. On the other hand, an equation is true only for certain values of its vari-
ables. An equation is not an identity.
11. The following are the standard identities:
(a + b)2 = a2 + 2ab + b2 …………………..(I)
(a – b) 2 = a2 – 2ab + b2 …………………….(II)
(a + b) (a – b) = a2 – b2 …………………….(III)
12. Another useful identity is (x + a) (x + b) = x2 + (a + b) x + ab (IV)
13. The above four identities are useful in carrying out squares and products of al-
gebraic expressions. They also allow easy alternative methods to calculate products
of numbers and so on.
Exercise 1
1. Identify the terms, their coefficients for each of the following expres-
sions.
(i) 5xyz2 – 3zy
Answer: 0.3 is the coefficient for a, for b there are two coefficients 0.6 and 0.5
Answer:
x + y: Binomial
1000: Mononomial
x + x2 + x3 + x4: Polynomial
7 + y + 5x: Binomial
2y – 3y2: Binomial
2y – 3y2 + 4y3: Trinomial
5x – 4y + 3xy: Trinomial
4z – 15z2: Binomial
ab + bc + cd + da: Polynomial
pqr: Mononomial
p2q + pq2: Binomial
2p + 2q: Binomial
(b) Subtract 3xy + 5yz – 7zx from 5xy – 2yz – 2zx + 10xyz
Answer: (5 xy − 2 yz − 2 zx + 10 xyz ) − (3 xy + 5 yz − 7 zx )
= 5 xy − 2 yz − 2 zx + 10 xyz − 3xy − 5 yz + 7 zx
= 2 xy − 7 yz + 5 zx + 10 xyz
Exercise 2
Answer: 4 × 7 p = 28 p
(ii) – 4p, 7p
Answer: − 4 p × 7 p = − 28 p ²
Answer: − 4 p × 7 pq = − 28 p ²q
(iv) 4p3, – 3p
Answer: 4 p ³ × − 3 p = − 12 p
(v) 4p, 0
Answer: 4p× 0 = 0
(ii) 2p × 4q × 8r = 64pqr
(iv) a × 2b × 3c = 6abc
Exercise 3
Answer: 4 p (q + r ) = 4 pq + 4 pr
(ii) ab, a – b
(iv) a² – 9, 4a
(v) pq + qr + rp, 0
Answer: ( pq + qr + rp )0 = 0
(iv) x × x² × x³ × x
=x14
1
3. (a) Simplify 3x (4x – 5) + 3 and find its values for (i) x = 3 (ii) x =
2
Answer: 3x(4x-5)+3
=12x²-15x+3
(b) Simplify a (a² + a + 1) + 5 and find its value for (i) a = 0, (ii) a = 1
(iii) a = – 1.
Answer: a(a²+a+1)
=a³+a²+a
Answer: p ( p − q ) + q (q − r ) + r (r − p )
= p ² - pq + q² - qr + r² - rp
= p ² + q² + r² - pq - qr - pr
Answer: 2 x( z − x − y ) + 2 y ( z − y − x )
= 2 xz − 2 x ² - 2xy + 2yz - 2y² - 2xy
= 2 xz − 2 xy + 2 yz − 2 x ² - 2y²
Exercise 4
Answer: (2 x + 5)(4 x − 3)
= 2x × 4x − 2x × 3 + 5 × 4x − 5 × 3
= 8 x ² - 6x + 20x - 15
= 8 x ² + 14x - 15
Answer: ( y − 8)(3 y − 4)
= y × 3y − y × 4 − 8 × 3y + 8 × 4
= 3 y ² - 4y - 24y + 32
= 3 y ² - 28y + 32
Answer: (a+b3)x5
= a × x + a × 5 + 3b × x + 3b × 5
= ax + 5a + 3bx + 15b
3 2
(vi) a ² + 3b² × 4 a ² - b ²
4 3
3 8
= a ² + 3b² 4a ² + b ²
4 3
3 3 8 8
= a ² × 4a² - a ² × b² + 3b² × 4a² - 3b² × b²
4 4 3 3
= 3a-2a²b²+12a²b²-8b
=3a+10a²b²-8b
Answer: (5 − 2 x )(3 + x)
= 5 × 3 + 5 × x − 2x × 3 − 2x × x
= 15 + 5 x − 6 x − 2 x ²
= 15 − x − 2 x ²
Answer: ( x + 7 y )(7 x − y )
= x × 7x − x × y + 7 y × 7x − 7 y × y
= 7 x ² - xy + 49xy - 7y²
= 7 x ² + 48xy - 7y²
Answer: ( p ² - q²)(2p + q)
= p ² × 2p + p²q - q² × 2p - q² × q
= 2 p ³ + p ²q - 2pq² - q³
3. Simplify.
(i) (x² – 5) (x + 5) + 25
Answer: ( x ² - 5)(x + 5) + 25
= ( x ² × x + 5 × x - 5 × x - 5 × 5) + 25
= x ³ + 5 x − 5 x − 25 + 25
= x³
Answer: (a ² + 5)(b³ + 3) + 5
= a ² × b³ + a² × 3 + 5 × b³ + 5 × 3
= a ²b ³ + 3a ² + 5b ³ + 15
Answer: (t + s ²)(t² - s)
= t × t ² - t × s + s² × t² - s² × s
= t ³ − ts + s ²t² - s³
Answer: ( x + y )(2 x + y ) + ( x + 2 y )( x − y )
= ( 2 x ² + xy + 2xy + y²) + ( x² - xy + 2xy - 2y²)
= 2 x ² + 3xy + y² + x² + xy - 2y²
= 3x ² + 4xy - y²
Answer: ( x + y )( x ² - xy + y²)
= x ³ − x ²y + xy² + x²y - xy² + y³
= x ³ + y³
(vii) (1.5x – 4y)(1.5x + 4y + 3) – 4.5x + 12y
(viii) (a + b + c)(a + b – c)
Answer: (a + b + c)(a + b − c)
= a ² + ab - ac + ab + b² - bc + ac + bc - c²
= a ² + b² - c² + 2ab
Exercise 5
1 1
(iv) 3a − 3a −
2 2
1
Answer: 9a ² - 3a + (same as previous question)
4
(v) (1.1m – 0.4) (1.1m + 0.4)
Answer: (a²+b²)(-a²+b²)
=(b²+a²)(b²-a²)
=b-a (same as previous question)
(viii) (– a + c) (– a + c)
Answer: (-a+c)(-a+c)
=(c-a)(c-a)
=c²+a²-2ac
x 3y x 3y
(ix) + +
2 4 2 4
Answer: ( x + 3)( x + 7)
= x ² + (3 + 7)x + 21
= x ² + 10x + 21
Answer: (4 x + 5)(4 x + 1)
= 16 x ² + (5 + 1)4x + 5
= 16 x ² + 24x + 5
Answer: (4 x − 5)(4 x − 1)
= 16 x ² + (-5 + -1)4x + (-5)
= 16x ² - 24x - 5
Answer: (4 x + 5)(4 x − 1)
= 16 x ² + (5 - 1)4x - 5
= 16 x ² + 4x - 5
Answer: (2 x + 5 y )(2 x + 3 y )
= 4 x ² + (5y + 3y)2x + 15y²
= 4 x ² + 8xy + 15y²
2 3
(iv) ( m + n) ²
3 2
4. Simplify.
(i) (a² – b²)²
5. Show that.
(i) (3x + 7)² – 84x = (3x – 7) ²
RHS: (9 p + 5q)²
= 81 p ² + 25q² + 90pq ……………………..(2)
Equations (1) & (2) prove that LHS = RHS
4 3 16 9
(iii) ( m − n)² + 2mn = m² + n²
3 4 9 16
4 3
Answer: LHS: ( m − n)² + 2mn
3 4
16 9
= m² + n² - 2mn + 2mn
9 16
16 9
= m² + n² = RHS Proved
9 16
(v) (a – b) (a + b) + (b – c) (b + c) + (c – a) (c + a) = 0
(ii) 99²
(iii) 102²
(iv) 998²
(v) 5.2²
300² - 3²
= 90000 − 9 = 89991
(vii) 78 × 82
(iii) 103 × 98
Answer: 103× 98
= (90 + 13)(90 + 8)
= 90² + (13 + 8)90 + 13 × 8
= 8100 + 1890 + 104
= 10094
Answer: 9 .7 × 9 .8
= (9 + 0.7)(9 + 0.8)
= 9² + (0.7 + 0.8)9 + 0.7 × 0.8
= 81 + 13.5 + 0.56
= 95.05